Lang Man behind the Scenes: Patriarchy in a Yaoi Novel - Juhong, Nonthikan; Piayura, Orathai (Dhammathas Academic Journal, 2023)
This research examines the Yaoi novel Lang Man Behind the Scenes for: 1) uses of patriarchal power and 2) evidence of defiance against patriarchal power. The research is designed as a qualitative research. The study applied Kate Millett’s conceptual framework on patriarchy. The results were as follow: 1. Patriarchal power and defiance against it could be characterized in four different contexts: 1) the use of father’s authority in the family between father and child; 2) in university and work settings based on seniority, among friend groups, and between supervisors and subordinates; 3) between the male protagonists; and 4) between male and female characters. 2. The novel showed evidence of defiance against patriarchal power in all four of the aforementioned contexts. 1) Defiance against uses of patriarchal power in the family occurres between the father and child and between the father and mother. 2) Defiance against uses of patriarchal power in the university and work setting occurs within both the seniority and the supervisor-subordinate systems. The novel also portrays defiance against uses of patriarchal power 3) between the male protagonists and 4) between male and female characters.